UVA students bring Architecture closer to both schools and families in Castilla y León - Ramón-Cueto, Gemma (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
There is a general decrease in the interest in architecture that makes it necessary to do initiatives with the aim of children and young people of all ages, and not just before entering university, knowing the profession and competencies that architects can develop. The main goal of this Innovation Project is to organize collaborative and multi-disciplinary procedures to bring architecture closer to both the educational centres in Castilla y León and to society. During the school year students, professors, researchers, administration staff and former Architecture students propose ludic and collaborative activities to do in non-university educational centres. The year ends with a Fair "Espacios de Ingenio" at our own University.